Principles of Restorative Justice: Settlement of Criminal Cases in Indigenous Peoples of Dukuh Village, Ciroyom Village - Cece Suryana (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2021)
In Indonesia there are still many community groups that still adhere to customary laws, one of which is the indigenous people of Kampung Dukuh, located in Ciroyom Village, Cikelet District, Garut Regency, West Java. One of the values of wisdom that is still maintained by these indigenous peoples is resolving problems related to criminal law violations by way of deliberation and providing a kind of offering or compensation to the victim which is called ngahaturanan pour (invites to eat) and then a peace occurs. between the perpetrator and the victim. The purpose of this research is to find out how the process of resolving criminal offenses in the Dukuh customary village is based on the principles of restorative justice and what is the role of law enforcement officials in handling criminal cases that occur in the Dukuh customary village area. The method that the authors use in this study is descriptive analysis method and uses normative juridical methods in its approach. The results of the study show the application of the principles of restorative justice in the settlement of criminal violations that occurred in the Dukuh traditional village, namely by conducting deliberations that aim to reconcile between the perpetrator and the victim, then the perpetrator also gives some compensation to the victim in the form of food and agricultural products it is called ngahaturanan pour (allowing to eat) then if the intention of peace made by the perpetrator to the victim is then accepted, then the perpetrator will be bathed by traditional leaders with certain prayers so that the sins of the perpetrator can be erased. The participation of law enforcement officials in dealing with cases of criminal violations that occur in the midst of the Dukuh Village customary community is to carry out a process of investigation and investigation of criminal cases which are felt to be handled directly by the police even though in reality the case has been resolved legally custom.